The headlight cloud in NGC 628: an extreme giant molecular cloud in a typical galaxy disk - Herrera, Cinthya N.; Pety, Jérôme; Hughes, Annie; Meidt, Sharon E.; Kreckel, Kathryn; Querejeta, Miguel; Saito, Toshiki; Lang, Philipp; Jiménez-Donaire, María Jesús; Pessa, Ismael; Cormier, Diane; Usero, Antonio; et al. (Astronomy and astrophysics, 2020)
Context. Cloud-scale surveys of molecular gas reveal the link between giant molecular cloud properties and star formation across a range of galactic environments. Cloud populations in galaxy disks are considered to be representative of the normal star formation process, while galaxy centers tend to harbor denser gas that exhibits more extreme star formation. At high resolution, however, molecular clouds with exceptional gas properties and star formation activity may also be observed in normal disk environments. In this paper we study the brightest cloud traced in CO(2-1) emission in the disk of nearby spiral galaxy NGC 628. Aims. We characterize the properties of the molecular and ionized gas that is spatially coincident with an extremely bright H II region in the context of the NGC 628 galactic environment. We investigate how feedback and large-scale processes influence the properties of the molecular gas in this region. Methods. High-resolution ALMA observations of CO(2-1) and CO(1−0) emission were used to characterize the mass and dynamical state of the “headlight” molecular cloud. The characteristics of this cloud are compared to the typical properties of molecular clouds in NGC 628. A simple large velocity gradient (LVG) analysis incorporating additional ALMA observations of 13CO(1−0), HCO+(1−0), and HCN(1−0) emission was used to constrain the beam-diluted density and temperature of the molecular gas. We analyzed the MUSE spectrum using Starburst99 to characterize the young stellar population associated with the H II region. Results. The unusually bright headlight cloud is massive (1 − 2 × 107 M⊙), with a beam-diluted density of nH2 = 5 × 104 cm−3 based on LVG modeling. It has a low virial parameter, suggesting that the CO emission associated with this cloud may be overluminous due to heating by the H II region. A young (2 − 4 Myr) stellar population with mass 3 × 105 M⊙ is associated. Conclusions. We argue that the headlight cloud is currently being destroyed by feedback from young massive stars. Due to the large mass of the cloud, this phase of the its evolution is long enough for the impact of feedback on the excitation of the gas to be observed. The high mass of the headlight cloud may be related to its location at a spiral co-rotation radius, where gas experiences reduced galactic shear compared to other regions of the disk and receives a sustained inflow of gas that can promote the mass growth of the cloud.
Gesehen am 07.04.2020